Fasting Glucose Level Modulates Cell Surface Expression of CD11b and CD66b in Granulocytes and Monocytes of Patients with Type 2 Diabetes. (August 2013) - Horvath, Peter; Oliver, Stacy R.; Ganesan, Goutham; Zaldivar, Frank P.; Radom-Aizik, Shlomit; Galassetti, Pietro R.
Introduction: Cardiovascular complications are the leading cause of mortality in type 2 diabetes (T2DM), in which onset and progression of atherosclerosis is linked to chronic inflammation. Activation status of innate immune cells (granulocytes [Gc], monocytes [Mc]), as reflected by increased CD11b, CD66b, and other surface markers, increases their endothelial and cytokines/chemokines release. Whereas this inflammatory activation seems inversely related to poor glycemic control, the effect of acute spontaneous hyperglycemia on innate immune cell activation remains unclear. Methods: Expression of key markers (CD11b, CD14, CD16, CD62L, and CD66b) was therefore determined by flow cytometry on whole blood of healthy subjects and patients with T2DM with spontaneous fasting euglycemia or hyperglycemia both at baseline and after 30, 90, and 240 minutes of incubation at room temperature. Results: Hyperglycemic patients with T2DM had significantly higher Gc and Mc CD11b and Gc CD66b surface mean fluorescence intensity compared with the euglycemic patients with T2DM whose values were similar to those of the healthy controls. CD16 expression in CD14+CD16+ Mc was elevated in all patients with T2DM, regardless of glycemic levels. Conclusion: Our data suggest that whereas the presence of diabetes per se may have a proinflammatory effect, hyperglycemia seems to further acutely exacerbate innate cell inflammatory status and their consequent endothelial adhesion and vascular damage potential.